Genetic diversity of french bean (Phaseolus vulgaris L.) under water stress condition - Choudhury, AK; Karim, MA; Khaliq, QA; Haque, MM; Ahmed, JU; Hossain, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(1) June 2009 25-30